Experience with Arteriovenous Fistula in Elderly Patients with Chronic Kidney Disease - Ersoy, Güler Gülsen; Tamtekin, Burak; Taşkent, İsmail (Wiley, 2025)
ABSTRACTObjectivesIn recent years, advances in medical care have expanded the boundaries of aging, leading to an increasing number of elderly individuals requiring hemodialysis (HD). The use of arteriovenous (AV) fistulas for HD in elderly patients remains controversial due to concerns about life expectancy, vascular aging, and comorbidities. This study aimed to compare AVF outcomes in patients aged ≥ 70 years with those aged < 70 years to evaluate the safety and efficacy of AVFs in elderly patients.Materials and MethodsThis retrospective, single‐center study included 202 patients who underwent AVF creation for end‐stage kidney disease between 2022 and 2024. Patients were divided into two groups: ≥ 70 years (n = 76) and < 70 years (n = 126). AVF maturation, complication rates, the need for new AVF, and primary and secondary patency rates were compared. Kaplan–Meier analysis and the log‐rank test were used to assess patency outcomes.ResultsAVF maturation rates were comparable between the ≥ 70 years group (50.0%) and the < 70 years group (56.9%) (p = 0.330). The need for a new AVF within 6 months was 11.2% in the ≥ 70 years group and 17.6% in the < 70 years group (p = 0.387). There were no significant differences in late complications (p = 0.157), AVF location preferences (p = 0.450), or secondary intervention rates (p = 0.967). Kaplan–Meier analysis revealed no significant difference in primary (p = 0.411) or secondary (p = 0.432) patency between the two groups.ConclusionDespite age‐related concerns, AVF outcomes in elderly patients were comparable to those in younger individuals. AVFs should be considered a viable vascular access option for HD in elderly patients, provided that patient‐specific factors are taken into account.